1998
DOI: 10.1093/jnci/90.21.1637
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Socioeconomic Factors in Relation to Prostate Cancer Mortality: a Cross-National Study

Abstract: The specific food-related results from this study are consistent with previous information and support the current dietary guidelines and hypothesis that grains, cereals, and nuts are protective against prostate cancer. The findings also provide a rationale for future study of soy products in prostate cancer prevention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
170
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(177 citation statements)
references
References 35 publications
1
170
0
4
Order By: Relevance
“…Few epidemiologic studies have been conducted evaluating the association between nut consumption and cancer. An ecological study showed that prostate cancer mortality was inversely associated with nuts and oilseed consumption [27]. Moreover, findings from prospective studies suggest inverse associations between nut consumption and colorectal or endometrial cancer, especially in women [28]–[31].…”
Section: Discussionmentioning
confidence: 99%
“…Few epidemiologic studies have been conducted evaluating the association between nut consumption and cancer. An ecological study showed that prostate cancer mortality was inversely associated with nuts and oilseed consumption [27]. Moreover, findings from prospective studies suggest inverse associations between nut consumption and colorectal or endometrial cancer, especially in women [28]–[31].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Absorbance (450 nm The results of epidemiologic studies indicate that dietary factors may be the main reason that Western populations run a higher risk of prostate cancer than do Asian populations. 2,3 Recently, curcumin has become a focus of interest with regard to its possible antitumor effects in prostate cancer. [12][13][14][15][16][17][18] This study shows for the first time, to our knowledge, that curcumin exerts an inhibitory effect on the invasiveness of DU-145 prostate cancer cells, and confirms this via both in vitro and in vivo testing.…”
Section: Discussionmentioning
confidence: 99%
“…This difference has been proposed to be attributable to the dietary consumption of abundant amounts of plant-based foods in Asia, foods that are often also rich in phytochemicals. 2,3 The majority of prostate cancer deaths occur in patients exhibiting metastases. In order to metastasize, degradation of the extracellular matrix (ECM) and basement membrane must occur.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In general, foods rich in saturated fat and calories are considered as promoters of prostate cancer, 3,4 whereas vegetables and fruits, including selenium, vitamins A, E, D and C, and isoflavones are inhibitors. [5][6][7][8] It is strongly suggested that the recent significant increase in the incidence of prostate cancer, as well as cardiovascular diseases and diabetes mellitus in Japan may be due to the increased habitual consumption of high-calories high-fat food. Nonetheless, the morbidity of prostate cancer among the Japanese is still significantly lower than among the Caucasian, African and Hispanic people.…”
Section: Introductionmentioning
confidence: 99%